Safety and effects of two mistletoe preparations on production of Interleukin-6 and other immune parameters - a placebo controlled clinical trial in healthy subjects - Huber Roman; Lüdtke Holger; Wieber Johannes; Beckmann Christiane (BMC, 2011)
Abstract Background In Germany, Iscucin® Populi (IP), a preparation from mistletoe growing on the poplar tree, is used in cancer therapy while Viscum Mali e planta tota (VM), a preparation from mistletoe growing on the apple tree, is used in patients with osteoarthritis. Since mistletoe preparations are suspected to induce production of potentially tumor promoting cytokines like interleukin (IL)-6, further studies on the immunological effects are of interest. Methods In this 3-armed randomized, double blind clinical trial healthy volunteers received increasing doses of either IP (strength F, 0.0125%, G, 0.25% and H, 5%, each for 4 weeks), or VM (1:1000 [D3], 1:100 [D2] and 2% each for 4 weeks) or placebo (isotonic solution) subcutaneously twice per week over a period of 12 weeks. Physical examination was performed weekly. Routine laboratory parameters and immunological parameters (C-reactive protein (CRP), differential blood count, lymphocyte subsets, immunoglobulins, IL-6 and tumor necrosis factor (TNF)-α) were analysed every 4 weeks. Results 71 subjects were included in the study (IP = 30, VM = 21, placebo = 20) of whom 69 concluded it according to protocol. Application of IP strengths G and H caused strong local reactions at the site of injection. In parallel, a distinct eosinophilia (p < 0.001 compared to placebo) occurred. Furthermore, application of all IP concentrations resulted in an increase of CD4 cell counts (p < 0.05) compared to placebo. Stimulation of IL-6 production, CRP or relevant deviations in other laboratory parameters were not observed. Because of local reactions, IP strengths G and H were considered less tolerable than placebo. VM 2% was slightly less tolerable than placebo, caused only mild local reactions and an only small increase in eosinophile counts. Conclusion Treatment with IP results in eosinophilia and an increase of CD4 cells but not in an increase of IL-6 or CRP. No safety concerns regarding the two mistletoe preparations have been raised by this study. EudraCT-Number 2007-002166-35. Trial registration ClinicalTrials.gov: NCT01378702